RETRACTED: The essence of student and Pearson's mathematical-statistical method in the development of communicative culture of future teachers through project education - Farmonova Shabon (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001